2014
DOI: 10.3892/ijo.2014.2390
|View full text |Cite
|
Sign up to set email alerts
|

miR-181b increases drug sensitivity in acute myeloid leukemia via targeting HMGB1 and Mcl-1

Abstract: Abstract. Multidrug resistance (MDR) remains the major cause of disease relapse and poor prognosis in adults with acute myeloid leukemia (AML). Emerging evidence shows that drug resistance not only exists against conventional chemotherapeutic drugs, but also limits the efficacy of new biological agents. Therefore, it is important to elucidate the mechanisms through which AML patients develop drug resistance. MicroRNAs have been shown to play an important role in regulating the chemotherapy resistance in AML. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 41 publications
0
51
1
1
Order By: Relevance
“…16,17 MiR-181b was decreased significantly in human multidrug-resistant leukemia cells and increased the sensitivity of leukemia cells to cytotoxic chemotherapeutic agents. 18 MiR-381 and miR-495 modulated the MDR phenotype of leukemia K562/ ADM cells and were associated inversely with the expression of the MDR1 gene and its protein product, P-glycoprotein. 19 Altered expression of miR-331-5p and miR-27a were correlated with leukemia cell resistance and relapse.…”
mentioning
confidence: 99%
“…16,17 MiR-181b was decreased significantly in human multidrug-resistant leukemia cells and increased the sensitivity of leukemia cells to cytotoxic chemotherapeutic agents. 18 MiR-381 and miR-495 modulated the MDR phenotype of leukemia K562/ ADM cells and were associated inversely with the expression of the MDR1 gene and its protein product, P-glycoprotein. 19 Altered expression of miR-331-5p and miR-27a were correlated with leukemia cell resistance and relapse.…”
mentioning
confidence: 99%
“…Recently, in a similar study, it has been demonstrated miR181b (another family of this microRNA) increases drug sensitivity in AML by targeting HMGB1 and MCL -1. 51 In this report, the authors found modification of these genes in all three tested patients. AML comprises a heterogeneous group of malignancies with diverse origins.…”
Section: Discussionmentioning
confidence: 68%
“…The cytotoxic activity of the NK cells was measured by a conventional 4-h 51 Cr release assay by using triplicate cultures in round-bottom 96-well plates. Different E: T ratios were used as described earlier.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Group 1 characterized with high level of expression of sncRNAs, which associated with sensitivity to therapy. This group members are miRNA-181a, b; let-7f, miRNA-9*, miRNA-96, miRNA-135a, miRNA-409, miRNA-10, miRNA29b and miRNA-217 [72,73,[97][98][99][100]. Group 1 members act through activation of cellular differentiation, inhibition of leukemic cells proliferation and survival, regulation of cell cycle, inducing of apoptosis and suppression of migration and invasion.…”
Section: Sncrnas As Markers Of Therapeutic Resistance or Sensitivity mentioning
confidence: 99%